Macrophage extracellular vesicle-packaged miR-23a-3p impairs maintenance and angiogenic capacity of human endothelial progenitor cells in neonatal hyperoxia-induced lung injury - Xuan Wang; Fang Yao; Lingling Yang; Dongshan Han; Yali Zeng; Zilu Huang; Chuanzhong Yang; Bingchun Lin; Xueyu Chen (Stem Cell Research & Therapy, 2024)
Abstract Background Premature infants requiring mechanical ventilation and supplemental oxygen for respiratory support are at increased risk for bronchopulmonary dysplasia (BPD), wherein inflammation have been proposed as a driver of hyperoxia-induced injuries, including persistent loss of endothelial progenitor cells (EPCs), impaired vascularization and eventual alveolar simplification in BPD lungs. However, the underlying mechanisms linking these phenomena remain poorly defined. Methods We used clodronate liposomes to deplete macrophages in a mouse model of neonatal hyperoxia-induced lung injury to evaluate if EPC loss in BPD lungs could be an effect of macrophage infiltration. We further generated in vitro culture systems initiated with cord blood (CB)-derived CD34+ EPCs and neonatal macrophages either polarized from CB-derived monocytes or isolated from tracheal aspirates of human preterm infants requiring mechanical ventilation and oxygen supplementation, to identify EV-transmitted molecular mechanism that is critical for inhibitory actions of hyperoxic macrophages on EPCs. Results Initial experiments using mouse model identified the crucial role of macrophage infiltration in eliciting significant reduction of c-Kit+ EPCs in BPD lungs. Further examination of this concept in human system, we found that hyperoxia-exposed neonatal macrophages hamper human CD34+ EPC maintenance and impair endothelial function in the differentiated progeny via the EV transmission of miR-23a-3p. Notably, treatment with antagomiR-23a-3p to silence miR-23a-3p in vivo enhances c-Kit+ EPC maintenance, and increases capillary density, and consequently mitigates simplified alveolarization in BPD lungs. Conclusion Our findings highlight the importance of pulmonary intercellular communication in the pathophysiology of BPD, by identifying a linkage through vesicle transfer of miR-23a-3p from hyperoxic macrophages to EPCs, and thus demonstrating potential for novel therapeutic target in BPD.